Sifat Fisik dan Organoleptik Es Krim dengan Penambahan Labu Siam (Sechium edule): Physical and Organoleptic Properties of Ice Cream with the Addition of Chayote (Sechium edule) - Faridah, Rajmi; Rahman, Abdul; Khaeruddin; Hermawansyah; Astuti, Tri (Anoa: Journal of Animal Husbandry, 2023)
During its development, ice cream is in great demand by the public, especially among children. Chayote, apart from having high nutrition, is also easy to obtain, so it is used to add ice cream.This study aims to determine the physical properties (Overrun and melting resistance) and organoleptic/ acceptability (color, aroma, texture, taste and preference) of ice cream with the addition of chayote. This study used a completely randomized design (CRD) with 4 level of chayote addition (0%, 10%, 20% and 30% addition of chayote) with 3 repetitions for physical tests (Overrun and melting resistance) while organoleptic tests (color, aroma, texture, taste and preference) with 25 repetitions using semi-trained panelists. The results of this study indicate that the addition of chayote to ice cream has a significant effect on physical properties, namely overrun and melting resistance also had a significant effect on organoleptic tests including color, aroma, taste and preference but had no significant effect on the texture of ice cream.